Spesifikasi Lingkungan Belajar Di Luar (Outdoor) - Virda Syaripatunisa; Rika Nurhayati; Risbon Sianturi (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2022)
The principle of PAUD is playing while learning. Children will be bored if they continue to study indoors, so there is learning outside the room to reduce child boredom. The process and method of PAUD teachers in structuring the outside learning environment need to pay attention to several specifications that can allow learning outside the room. This article was written with the aim of recommending to readers regarding the specifications of the outdoor learning environment. This article is reviewed using a literature study method based on a literature review, analyzing several reliable sources such as journal articles and books. The specifications of the environment for outdoor learning or playing are adapted to the circumstances of each PAUD school and made as creative as possible by the PAUD teachers themselves. Comfort for children in the facilities that have been provided at school also depends on the children themselves. Therefore, teachers must be able to deal with this and try to provide comfort to their children by paying attention to the specifications of this outdoor learning environment.ABSTRAKPrinsip PAUD yaitu bermain sambil belajar. Anak-anak akan jenuh jika terus menerus belajar didalam ruangan, maka adanya belajar diluar ruangan untuk mengurangi kejenuhan anak. Proses dan cara guru PAUD dalam penataan lingkungan belajar diluar perlu memperhatikan beberapa spesifikasi yang dapat memungkinkan belajar diluar ruangan. Artikel ini ditulis bertujuan untuk merekomendasi kepada pembaca mengenai spesifikasi lingkungan belajar diluar ruangan. Artikel ini dikaji menggunakan metode studi literatur didasarkan pada tinjauan literature, menganalisis beberapa sumber yang dapat dipercaya seperti artikel jurnal dan buku. Spesifikasi lingkungan untuk belajar atau bermain outdoor disesuaikan dengan keadaan masing-masing sekolah PAUD dan dibuat sekreatif mungkin oleh guru-guru PAUD itu sendiri. Kenyamanan pada anak-anak pada fasilitas yang sudah disediakan disekolah juga tergantung anak-anak itu sendiri. Oleh karena itu guru harus bisa menghadapi hal tersebut dan berusaha memberikan kenyamanan tergadap anak-anaknya dengan memperhatikan spesifikasi lingkungan belajar diluar ini.